Crash : Sebuah Kajian tentang Kemarahan - Febby Pratama Putra; Laila Desnaranti (LITERATUS, 2023)
The objective of this study is to examine the anger in Paul Haggis's film Crash. The author of this study identifies the sources and manifestations of anger in the film Crash. The author employs a descriptive qualitative approach. In order to evaluate the data, and explain anger, and the reasons and styles of anger, the writer uses a number of theories that have been put forth by the experts as a foundation. According to the writer, "insult," "out of control," "social triggers," "physical threat," "stress," "being a recipient of another person's anger," and "disappointment" are the main causes of anger in the movie Crash. As the author looks into the causes of anger, he discovers that the "aggressive style," "passive style," and "assertive style" of anger are all present in the film Crash. The analysis's findings show that: (1) Most of the characters in the film Crash become angry when those around them do something intentionally wrong; and (2) The characters utilize "aggressive style," "passive style," and "assertive style" to vent their anger.